Analisis Manajemen Penyelenggaraan Makanan di Instalasi Gizi RSUD Kardinah Tegal - Khasanah, Arini Noor (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Food is a source of energy which is processed and metabolized into energy. People who are sick need adequate food according to their needs and illness. Serving nutritious food is something that needs attention to support patient health. The need to understand the food delivery system in a hospital can provide an overview of how food is processed according to standards. Objective: Explain the food management system in the nutrition installation at Kardinah Hospital, Tegal. Methods: This article is a type of qualitative research that provides a description of the hospital food delivery process. Sources of data obtained from primary data in the form of interviews and secondary data in the form of documentation and work records. Results: The form of food delivery at Kardinah Hospital is a form of self-management where the process is managed by the hospital. The process flow is menu planning made by a nutritionist according to the budget and needs; procurement and ordering of materials ordered directly to partners, storage of food ingredients according to class and temperature; preparation of foodstuffs and tools; food processing according to standard; presentation and distribution with centralized and decentralized systems. Conclusion: Food management at Kardinah Hospital has met standards in several processes.